Newly Synthesized Hepatitis C Virus Replicon RNA Is Protected from Nuclease Activity by a Protease-Sensitive Factor(s) - Yang, Guang (American Society for Microbiology, 2004)
Biochemical characterization of hepatitis C virus (HCV) replication using purified, membrane-associated replication complexes is hampered by the presence of endogenous nuclease activity that copurifies with the replication complex. In this study, pulse-chase analyses were used to demonstrate that newly synthesized replicon RNA was protected from nuclease activity by a factor(s) that was sensitive to 0.5% NP-40 or protease treatment. Nuclease susceptibility was not related to disruption of lipid membranes, since NP-40 did not significantly affect the buoyant density of HCV replication complexes or protease susceptibility of HCV NS3 and NS5A proteins. These results suggest that a protease-sensitive factor(s) protects newly synthesized RNA from nuclease degradation.